Validity of Initial Clinical Diagnosis of Unstable Angina Based on the Invasive and Noninvasive Studies - Mohammad Hasan Namazi; Fatemeh Omidi (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
Introduction: A few studies have focused on diagnostic performance of residents for controlling the patients with acute chest pain referring to chest pain units. We aimed to assess diagnostic performance of cardiology residents for controlling the patients with acute chest pain, considering invasive and non-invasive diagnostic modalities as the key standards to confirm or refuse diagnosis of unstable angina.Methods: One hundred and twenty nine patients with chest pain or angina referring to chest pain unit of Modarres hospital between 2013 and 2014 were assessed. The patients were categorized into two subgroups. The first group included 23 patients who were discharged by the resident in initial evaluation because of ruling-out diagnosis of unstable angina, but were assessed non-invasively by exercise test or SPECT as key standards. The second group included 106 patients who were hospitalized and admitted to CCU by residents’ order and also were assessed invasively by coronary angiography or noninvasively by exercise test or SPECT.Results: Overall, of 129 patients, 23 were initially diagnosed not to be necessarily hospitalized and thus were discharged by resident’s order. Of those, assessing by SPECT indicated positive result in five of 19 patients and by exercise test indicated positive result in 1 of 4 patients yielding a sensitivity of 83.3%, a specificity of 17.6%, a PPV of 26.3%, a NPV of 75.0%, and an accuracy of 34.8% for assessing disease by resident. The remaining 106 patients were admitted to CCU ward in accordance with the resident’s order. Among those patients, 85 underwent coronary angiography with positive results in 53 patients. Also, SPECT was positive in 10 of 19 patients and exercise test was positive in one of two patients yielding a sensitivity of 95.3%, a specificity of 0.0%, a PPV of 59.2%, a NPV of 0.0%, and an accuracy of 57.5%.Conclusions: For patients with suspicion to unstable angina, the decision of residents in chest pain units for discharging or admitting patients suspected to unstable angina is accompanied with high sensitivity but unacceptable specificity and thus using supplement diagnostic tools such as exercise test or SPECT can be very helpful for diagnosing unstable angina.